Films with legs : crossing borders with foreign language films - Peters, Rosemary A.; Maisier, Véronique (Cambridge Scholars Pub., 2011)
Films With Legs: Crossing Borders with Foreign-Language Films addresses the ways in which international cinematic traditions both erect borders and blur them or tear them down. Each chapter of this book examines both real and perceived borders, their representation on the screen and the ways in which they manifest in filmic texts that can also be cultural documents and political statements. The fifteen articles included here discuss films made by twenty-four directors, with dialogue in nine f ...